2022
DOI: 10.3390/cancers14051192
|View full text |Cite
|
Sign up to set email alerts
|

Neratinib and Capecitabine for the Treatment of Leptomeningeal Metastases from HER2-Positive Breast Cancer: A Series in the Setting of a Compassionate Program

Abstract: Background: Leptomeningeal metastasis is a neurological complication from HER2-positive breast cancer with a poor prognosis and limited treatment options. This study has evaluated the activity of neratinib in association with capecitabine in 10 patients with LM from HER2-positive BC after the failure of multiple lines of treatment, including trastuzumab-based therapy, within a compassionate program, and a comparison was made with a historical control group of 10 patients. Methods: Patients aged ≥ 18 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In line with the previous findings, the most frequent treatment-related AEs for pyrotinib were diarrhea and hand-foot syndrome. Two trials reported that treatment with neratinib plus capecitabine is useful for HER2-positive breast cancer with brain metastases (Cunningham et al, 2022;Pellerino et al, 2022). The results for PFS, OS, and AEs are similar to data from previous trials.…”
Section: Irreversible Tkis Plus Chemotherapy Vs Other Regimenssupporting
confidence: 73%
See 2 more Smart Citations
“…In line with the previous findings, the most frequent treatment-related AEs for pyrotinib were diarrhea and hand-foot syndrome. Two trials reported that treatment with neratinib plus capecitabine is useful for HER2-positive breast cancer with brain metastases (Cunningham et al, 2022;Pellerino et al, 2022). The results for PFS, OS, and AEs are similar to data from previous trials.…”
Section: Irreversible Tkis Plus Chemotherapy Vs Other Regimenssupporting
confidence: 73%
“…The results for PFS, OS, and AEs are similar to data from previous trials. Moreover, treatment with neratinib plus capecitabine significantly improves survival outcomes compared with the use of intrathecal Ara-C or whole-brain radiotherapy (WBRT) (Pellerino et al, 2022). Findings from the NEfERT-T (Awada et al, 2016) trial indicate that although the overall efficacy of neratinib-paclitaxel and trastuzumab-paclitaxel is similar, the neratinib-paclitaxel combination may delay central nervous system (CNS) progression.…”
Section: Irreversible Tkis Plus Chemotherapy Vs Other Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Only select anti-HER2 therapies have reported activity in HER2 + LM. In particular, neratinib plus capecitabine showed preliminary activity in LM, with median LM-PFS of 4 months and OS of 10 months 13 . In addition, the use of intrathecal trastuzumab has demonstrated ORR of 19.2%, SD in 50%, with a CBR of 70%, and median-OS of 10.5 months 14 .…”
mentioning
confidence: 99%
“…Neratinib, a HER2-targeting tyrosine kinase inhibitor combined with capecitabine, demonstrated promising intracranial activity in patients with HER2 overexpressing breast cancer [70]. There are case series of efficacy in leptomeningeal metastases [71]. Preliminary results from a phase II trial evaluating the effectiveness of the combination of tucatinib-trastuzumabcapecitabine in the treatment of NM from HER2+ breast cancer have reported a median OS of 11.9 months in a cohort of 17 patients (NCT03501979) [72].…”
Section: Targeted Therapiesmentioning
confidence: 99%